JUAL BELI TANAMAN KRATOM DI DESA KALIS RAYA KECAMATAN KALIS KABUPATEN KAPUAS HULU PERSPEKTIF EKONOMI ISLAM - Juli Anita (CV. Adiba Aisha Amira, 2023)
This research is based on the phenomenon of buying and selling kratom plants in Kalis Raya Village, Kalis District, Kapuas Hulu Regency. Where researchers are interested in researching buying and selling activities from an Islamic economic perspective. The focus of this study is 1) What is the phenomenon of buying and selling kratom plants in Kalis Raya village, Kalis District, Kapuas Hulu Regency? 2) How is it legal to buy and sell kratom plants? This research uses a qualitative approach with a descriptive type of research. data collection techniques with interviews, observations, and documentation. The results of this study show that there is a delay in payments from consumers abroad, the number of other supplayers who sell low prices with poor quality, the presence of Covid-19 cases which greatly hinder the process of shipping goods abroad. The law of buying and selling kratom plants in an Islamic economic perspective is allowed or mubah. All transactions that occur in the field, be it from farmers, employees and kratom factory owners, if they are associated with the theory of buying and selling and Islamic Economic law then what they carry out is in accordance with Islamic law